Glutathione: Role in Oxidative/Nitrosative Stress, Antioxidant Defense, and Treatments. Issue 18 (12th May 2021) - Raj Rai, Sristi; Bhattacharyya, Camelia; Sarkar, Anwita; Chakraborty, Surupa; Sircar, Esha; Dutta, Sreejita; Sengupta, Rajib
Abstract: Glutathione (GSH) is the most abundant cellular tripeptide (L‐γ‐glutamate‐L‐cysteinyl‐glycine) which is as critical as oxygen and water. This low molecular mass antioxidant has a very high intracellular concentration that ranges from 1–10 mM and reaches extreme concentration points in malignant cell types. This defender of the cell is compartmentalized in mitochondria, nucleus, peroxisomes, endoplasmic reticulum (ER), and cytosol where it is synthesized. The enzymes involved in GSH redox cycling are important for both cellular free radical and non‐radical detoxification. The present review article is covering the crucial roles of GSH to combat oxidative/nitrosative stress related to different diseases/disorders and possible drug designing for new therapies. Abstract : Glutathione is the most potent weapon against oxidative and nitrosative stress that results from a free radical overload. The concerted efforts of Glutathione along with a plethora of other antioxidants and denitrosylases serve to preserve the functions of several vital proteins that are susceptible to oxidative damage, thereby rescuing cells from stress induced apoptosis. The role of Glutathione as an antioxidant in other organisms can also not be undermined, and forms an active area of research in recent years. Many lines of therapy already are based on oral or intranasal administration of Glutathione, with the aim of retarding the progression of various diseases. The present review article is covering the crucial role of Glutathione to combat oxidative/nitrosative stress‐related different diseases/disorders and possible drug designing for new therapies.